Effectiveness of Slow Motion Back Massage on Reducing Dysmenorrhea Intensity: Literature Review - Dheby Dheirani; Okta Putri Ramdhani; Baiq Zuyyinah Khairawati; Dini Nur Alpiah (Publikasi Indonesia, 2024)
A common problem faced by adolescents during menstruation is primary dysmenorrhea. Symptoms include pain in the lower abdomen that can radiate to the back, waist, and thighs and interfere with activities. There is an effective treatment method to reduce pain intensity and reduce anxiety levels, namely by giving Slow Stroke Back Massage. The purpose of this study was to determine the effect of Slow Stroke Back massage on dysmenorrhea intensity. The research method used by the author is a literature review. This research is based on a literature review using a PICO search in several databases such as Google Scholar, Pubmed, and ResearchGate. 5 journals meet the criteria and get reports that giving Slow Stroke back massage which is done every day with a duration of 20 minutes if the intensity still occurs. After undergoing the intervention, a significance value with a p-value <0.05 was obtained. It can be concluded that it shows significant results in reducing pain intensity. The implications of this study may provide guidelines for health practitioners, especially massage therapists or reproductive health professionals, in integrating SSBMs as part of the care of patients with dysmenorrhea. It can improve understanding and acceptance of nonpharmacological therapies and may form the basis for continued research in the field of nonpharmacological therapies for dysmenorrhea.